Effect of strain profiling on anisotropic opto-electronic properties of As2X3 (X =S, Te) monolayers from first principles - Andharia, Eesha; Alqurashi, Hind; Erikat, Ihsan; Hamad, Bothina; Manasreh, M. O. (Frontiers in Materials, 2024)
Abstract: Strain Engineering is a widely adopted approach to modulate the opto-electronic performance of 2-Dimensional (2D) materials. Recently, anisotropic Van der Waals (vdW) based 2D As2S3 monolayer has gained significant attention within the scientific community due to its stability in ambient conditions. Similar compounds like As2Te3 have also been theoretically explored. However, its indirect bandgap nature limits its application in optical devices. In this study, a systematic study of compressive and tensile strain on three profiles – Uniaxial along a-axis, Uniaxial along b-axis and biaxial strain from -10% to +10%, is performed for As2S3 and As2Te3 monolayers. Certain strain profiles like Uniaxial tensile strain of 8% along b-axis results in transition to direct bandgap material. Similarly, for As2Te3, shear strain of (-10%, +8%) along (a, b) axis results in direct bandgap material. In addition, the anisotropic optical absorption spectrum is obtained for unstrained and strained monolayers within the random phase approximation (RPA).